The interplay of digital transformation, agility, environmental volatility, and innovation to spur enterprise performance: Evidence from Chinese electric vehicle firms - Boonsub Panichakarn; Jessada Pochan; Muhammad Shafiq; Irfan Saleem; YanQing Wang; Sonia Nazeer (Journal of Open Innovation: Technology, Market and Complexity)
Given the rapid growth of China's electric vehicle (EV) industry, with sales expected to reach over 10 million units annually by 2025, there is an urgent need to understand how digital logistics, supply chain agility, and innovation can drive sustainable performance amidst increasing environmental volatility. This study utilises the dynamic capability theory and proposes a framework that examines the interplay between digital transformation, agility, dual innovation, environmental volatility, and enterprise performance. A survey was circulated among the managers working in the EV industry. We received 197 responses. The data was analysed using Smart PLS software using structural equation modelling (SEM). The findings reveal that digital transformation has significant positive relationships with enterprise performance, agile capability, and innovation capability. Additionally, agile and innovation capabilities have positive effects on enterprise performance. The study recommends investment in digital transformation programs and fostering an agile, innovative culture in the EV industry.